2015
DOI: 10.1590/0103-8478cr20131494
|View full text |Cite
|
Sign up to set email alerts
|

Abundância e sazonalidade do ácaro-rajado em cultivares de gérbera

Abstract: Neste estudo foi avaliada a abundância e a sazonalidade de Tetranychus urticae Koch, 1836 em três cultivares de Gerbera jamesonii Adlam., em cultivo comercial no sul do Brasil. Para avaliação destes parâmetros foram realizadas amostragens de abril de 2011 a fevereiro de 2012. Os ácaros foram obtidos a partir de flores e folhas retiradas de cada uma das cultivares. No total foram contabilizados 10.640 ácaros e de acordo com os testes, a cultivar "Pink Snow" apresentou maior abundância significativa. A análise e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Campos-Farinha (2006) reports that sucking insects are among the main arthropods that damage ornamental plants and can, on many occasions, be easily found associated with these plants. In addition to these insects, the spider mite is an important pest in ornamentals and potted flowers (Tamai et al, 2000, Feres et al, 2009Santos et al, 2010;Sulzbach et al, 2015). According the figure 2, December was the month with major number of infested plants (n= 17).…”
Section: Resultsmentioning
confidence: 99%
“…Campos-Farinha (2006) reports that sucking insects are among the main arthropods that damage ornamental plants and can, on many occasions, be easily found associated with these plants. In addition to these insects, the spider mite is an important pest in ornamentals and potted flowers (Tamai et al, 2000, Feres et al, 2009Santos et al, 2010;Sulzbach et al, 2015). According the figure 2, December was the month with major number of infested plants (n= 17).…”
Section: Resultsmentioning
confidence: 99%
“…The Gerbera (G. jamesonii L. ) is one of the most important ornamental species for the cut flowers sector (Cardoso & Imthurn, 2018), and is traditionally known for its variety of colors and shapes (Bashandy et al, 2015). The flower is among the most commercialized cut flowers in the national market and its beauty causes consumer acceptance (Menegaes et al, 2015;Sulzbach et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cotton, gerbera, strawberry, tomato and papaya cultivars have demonstrated that significant differences in the population fluctuation of T. urticae might occur in varieties of different genotypes (Lourenção et al 2000, Maruyama et al 2002, Esteves Filho et al 2010, Moro et al 2012, Sulzbach et al 2015). These differences can be attributed to different volatile types produced by plants when attacked by phytophagous mites (Dicke 1988, Pallini et al 1997.…”
mentioning
confidence: 99%
“…In the present study, the mite density was low when compared to studies using other commercial crops. Sulzbach et al (2015) observed an average density of 25.5 mites per gerbera leaf in Três Irmãos County, RS, and Noorbo et al (2018) recorded an average population of 8.5 to 15.0 mites/leaf in 20 varieties of roses, yet for a better comparison, it is necessary to consider the leaf area of each species.…”
mentioning
confidence: 99%